THE EFFECT OF MILITANCY ON EDUCATION AND ITS SOCIO-ECONOMIC CONSEQUENCIES : (A Case Study of Tehsil Safi and Halimzai of Mohmand Agency) - Nawab, Sher; Ullah, Sami; Farooq, Usman; Malik, Muhammad Shafi; Ghafoor, Irshad (Journal of Education Culture and Society, 2021)
Background: The study was conducted in 2017 to know about the effects of militancy on education in the form of dropout from schools, destroyed infrastructure of educational institutions, decrease in literacy rate and to probe out the community perception about education in the context of adverse law and order situation in district Mohmand Agency. The study was significant because Mohmand Agency is the worst terrorist affected area. Objectives: The objectives of the study were examining the factors causing militancy, and to determine the effects of militancy on education in Mohmand Agency. Methodology: For this purpose, 250 sample respondents out of the total population from four selected villages viz Gurbaz, Masood, Sultan Khel and Baro Khel from tehsil Safi and Halimzai were selected. The respondents were randomly interviewed through an interview schedule. Chi-square test was used as statistical instrument to determine the association between education and different factors that cause terrorism. Results: It was found that majority of the respondents were agreed that unemployment, poverty, drone attacks, unidentified Pak-Afghan border were the main factors that caused militancy in the area and had greatly affected the primary and secondary education in the area. Respondents were of the view that brutal activities against Muslims across the globe and presence of NATO forces in the region increased terrorism. Involvement of foreign intelligence agencies in our county and weak national security network to handle terrorist activities properly were the main causes of terrorism. Parents remain worried about their children’s education due to security threats and insufficient schools remaining in the area. Conclusion: It was concluded that due to insecurity, lack of infrastructure and insufficient schools; education in the area under study was greatly affected. The study suggested that bringing of peace and reasonable security measures against militants can rebuild the educational environment in the study area.